Translating close-up research into action: a critical reflection. Issue 3 (3rd May 2016) - Clegg, Sue; Stevenson, Jacqueline; Burke, Penny-Jane
Abstract: This paper argues that simple dissemination models do not work. One of the strengths of close-up research, with its emphasis on depth and understanding, is that it can identify why things are as they are and, by extension, when we identify wrongs seek to challenge them. The paper suggests, however, that making a difference is fraught with contradictions and that the translation from research to action is far from straightforward. We illustrate these tensions by reflecting on our experiences of conducting two projects for the UK Higher Education Academy. At the same time as exploring the slippages of translation and loss of criticality, however, we want to defend notion of praxis as theoretically informed change for critical social purposes. This involves a view of making a difference and research that moves beyond thinking of research as a discrete act and invokes the significance of corporate agency and the possibilities of acting collectively.